Risk factors of emergency cesarean section in pregnant women with severe placenta accreta spectrum: a retrospective cohort study - Zhao, Hu; Li, Xin; Yang, Shuqi; Liu, Tianjiao; Zhan, Jun; Zou, Juan; Lin, Changsheng; Li, Yalan; Du, Na; Xiao, Xue (Frontiers in Medicine, 2023)
Introduction Placenta accreta spectrum (PAS) may cause enormous and potentially life-threatening hemorrhage in the intrapartum and postpartum periods in emergency cesarean section. How to reduce the occurrence of emergency cesarean section in patients with severe PAS is the key to reducing the adverse outcomes of them. This study aimed to investigate the impact of emergency cesarean section on the perioperative outcomes of pregnant women with PAS and neonates, and also aimed to explore the risk factors of emergency cesarean section in pregnant women with PAS. Materials and methods A retrospective investigation was conducted among 163 pregnant women with severe PAS. Of these, 72 were subjected to emergency cesarean sections. Data on the perioperative characteristics of the mothers and neonates were collected. Multivariable linear regression analysis was used to detect associations between maternal and perioperative characteristics and volume of intraoperative bleeding. Binary logical regression was used to analyze the association between maternal preoperative characteristics and emergency cesarean section. Linear regression analysis is used to analyze the relationship between gestational age and emergency cesarean section. Results The risks of emergency cesarean section increase 98, 112, 124, and 62% when the pregnant women with PAS accompanied by GHD, ICP, more prior cesarean deliveries and more severe PAS type, respectively. Noteworthy, the risk of emergency cesarean section decreases 5% when pre-pregnancy BMI increases 1 kg/m2 (OR: 0.95; CI: 0.82, 0.98; p = 0.038). Moreover, there is no significant linear correlation between emergency cesarean section and gestational age. Conclusion GHD, ICP, multiple prior cesarean deliveries and severe PAS type may all increase the risk of emergency cesarean section for pregnant women with PAS, while high pre-pregnancy BMI may be a protective factor due to less activity level. For pregnant women with severe PAS accompanied by these high risk factors, more adequate maternal and fetal monitoring should be carried out in the third trimester to reduce the risk of emergency cesarean section.